Reconstruction of Radiated Gluteal Defects following Sarcoma Resection with Pedicled Sensate Tensor Fascia Lata Flaps - Albert H. Chao; Patrick N. Kearns (Case Reports in Oncological Medicine)
Sarcomas of the gluteal region often result in sizable defects following resection that are challenging to reconstruct due to their location, particularly in patients who have received radiation therapy. Reconstruction of these defects has been seldom discussed in the literature. We present two patients with large radiated gluteal defects following sarcoma resection, of which one patient received neoadjuvant radiation and the other received intraoperative radiation therapy. As a result of the resection and radiation, local tissues and recipient vessels were unsuitable for use in reconstruction. A pedicled tensor fascia lata (TFL) flap was therefore performed in both cases, which resulted in durable sensate reconstruction with good functional outcomes and no complications. We believe the pedicled TFL flap represents an important option for the reconstruction of oncologic gluteal defects that provides well-vascularized and sensate tissue from outside the zone of radiation without the need for microsurgical techniques.